Prevalence of depressive symptoms in urban primary care settings: Botswana - Keneilwe Motlhatlhedi; Keneilwe Molebatsi; Grace N. Wambua (AOSIS, 2021)
Background: The prevalence of depression is estimated to be high in primary care settings, especially amongst people with chronic diseases. Early identification and management of depression can improve chronic disease outcomes and quality of life, however, there are many missed opportunities in primary care. Aim: This study aimed to determine the prevalence and correlates of depression and depressive symptoms in two urban primary care settings. Setting: The study was conducted at two primary care facilities in the capital city of Botswana. Methods: We administered a demographic questionnaire and the Patient Health Questionnaire-9 (PHQ-9) to adults attending two primary care facilities. The association between depressive symptoms and demographic variables was determined using Chi-square; level of significance was set at 0.05. We carried out a multivariate analysis using Kruskal-Wallis test to determine the association between demographic characteristics and depression. Results: A sample of 259 participants were recruited (66.8% women, median age 32). The mean PHQ-9 score was 8.71. A total of 39.8% of participants screened positive for depression at a cut-off of 9.0% and 35.1% at a cut-off of 10. Depressive symptoms were significantly associated with employment status and income using the Kruskal-Wallis test, χ2 (1) = 5.649, p = 0.017. Conclusion: The high rates of depressive symptoms amongst the study population highlight the need for depression screening in primary care settings. The association between unemployment and income underscore the impact of socio-economic status on mental health in this setting.